2018
DOI: 10.1016/j.cmet.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Impairing L-Threonine Catabolism Promotes Healthspan through Methylglyoxal-Mediated Proteohormesis

Abstract: Whether and how regulation of genes and pathways contributes to physiological aging is topic of intense scientific debate. By performing an RNA expression-based screen for genes downregulated during aging of three different species, we identified glycine-C-acetyltransferase (GCAT, EC 2.3.1.29). Impairing gcat expression promotes the lifespan of C. elegans by interfering with threonine catabolism to promote methylglyoxal (MGO; CAS 78-98-8) formation in an amine oxidase-dependent manner. MGO is a reactive dicarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 85 publications
5
59
0
Order By: Relevance
“…These observations are in line with mitohormesis, a concept described in multiple organisms 18,57 whereby a moderate increase in ROS production, in the low micromolar range (Fig. 3f), promotes stress resistance and longevity 20,58 . This hypothesis is supported by recent literature pointing to the signaling role of ROS 16,17 .…”
Section: Discussionsupporting
confidence: 84%
“…These observations are in line with mitohormesis, a concept described in multiple organisms 18,57 whereby a moderate increase in ROS production, in the low micromolar range (Fig. 3f), promotes stress resistance and longevity 20,58 . This hypothesis is supported by recent literature pointing to the signaling role of ROS 16,17 .…”
Section: Discussionsupporting
confidence: 84%
“…Next, we asked whether these transcription factors are also needed for the promotion of proteostasis by reducing the cav-1 expression levels. Importantly, all three transcription factors were shown to promote proteostasis in previous studies [13,45] and inhere (Appendix Fig S4). Ab worms were treated with mixtures of RNAi toward cav-1 and each transcription factor as described above, and the rates of paralysis within the worm populations were recorded.…”
Section: Reduced Cav-1 Expression Promotes Proteostasis By Inducing Tmentioning
confidence: 67%
“…Importantly, all three transcription factors were shown to promote proteostasis in previous studies [13,45] and inhere (Appendix Fig S4). Importantly, all three transcription factors were shown to promote proteostasis in previous studies [13,45] and inhere (Appendix Fig S4).…”
mentioning
confidence: 67%
“…Loss of function of GLOD-4, on the other hand, shortens lifespan which is exacerbated under high glucose conditions in C. elegans (Chaudhuri et al, 2016). Interestingly, a recent study has shown that low concentrations of MGO, formed via inactivation of the enzyme glycine-C-acetyltransferase (GCAT) involved in threonine catabolism, can promote lifespan through proteohormesis (Ravichandran et al, 2018). Reduction of age-related accumulation of AGEs by the FDA-approved (for the treatment of tuberculosis (TB)) drug Rifampicin also enhances worm lifespan through activation of DAF-16/FOXO (Golegaonkar et al, 2015).…”
Section: The Maillard Reaction: Initiators Propagators and Chemistrymentioning
confidence: 99%